Characteristics of Hemodialysis Patients Due to Chronic Kidney Failure in 2018-2022 at Santa Elisabeth Medan Hospital - Juni Setianus Baeha; Rotua Elvina Pakpahan; Agustaria Ginting (Sean Institute, 2025)
Cronic kidney failure causes a decrease in glomerular filtration, resulting in the kidneys being unable to remove toxins and producing blood waste so that toxins in the body cannot be removed and circulate in the bloodstream and cause excess body fluids. Blood circulation containing toxic substances can cause various health complaints and can even lead to death, so medical management in the form of hemodialysis is needed to help the glomerulus filter toxic substances, fluids and electrolytes. This study aims to identify the characteristics of chronic kidney failure patients in 2018-2022 who underwent hemodialysis at the Santa Elisabeth Hospital. The study was descriptive in nature using secondary data from medical records. The study population was 24,288 people, with a sample of 100 people, where the sample was taken based on the proportional random sampling technique. Research data was taken from the patient status in the medical record room and hemodialysis room using a checklist sheet. The results showed that 41% of patients were >60 years old, male gender 58%, high school education 62%, unemployed 31%, duration of HD <12 months 60%, and hypertension as the cause of GGK 76%. It is expected that hospitals emphasize recording patient data in the medical record room carefully and completely, to facilitate access to patient data when needed for research and legality needs.